2011
DOI: 10.2514/1.49490
|View full text |Cite
|
Sign up to set email alerts
|

Progress on the Physical Approach to Molecular Contamination Modeling

Abstract: A review of the contamination physics and of the most widespread engineering approaches to contamination assessment was carried out. The two main approaches are the physical and the empirical one. The main questions still open to validate the physical approach to outgassing and deposit physics were then studied. Among others, special attention was paid to the important point of a realistic separation of chemical species, probably a prerequisite for a physical modeling. Several original results were obtained. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Introduction I N-FLIGHT spacecraft contamination is driven by four main phenomena: contaminant generation (outgassing, propulsion, etc. ), transport, reemission, and fixation by space radiation [1,2]. No correct in-flight contamination assessment can be produced if one of these phenomena is neglected.…”
Section: Nomenclature Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction I N-FLIGHT spacecraft contamination is driven by four main phenomena: contaminant generation (outgassing, propulsion, etc. ), transport, reemission, and fixation by space radiation [1,2]. No correct in-flight contamination assessment can be produced if one of these phenomena is neglected.…”
Section: Nomenclature Cmentioning
confidence: 99%
“…Temperature dependence for pure contaminant evaporation is given by the Clausius-Clapeyron law. As a result, the evaporation rate of a pure contaminant is almost an Arrhenius law characterized by an activation energy and a preexponential factor [1,2]. We previously showed that this simple description can be insufficient to describe reemission of a deposit generated by vacuum deposition, for two main reasons.…”
Section: Nomenclature Cmentioning
confidence: 99%
“…Whereas the temperature of a spacecraft surface facing away from the sun can fall below -20 • C, outgassed deposits have a high probability of sticking. To prevent this contamination, materials for use in space are screened in accordance with established standards [9], [10] and simulation tools that emulate both outgassing and deposition kinetics to assess the amount of contaminant deposition in orbit [11], [12]. The QCM sensor is widely used to assess the deposition/desorption amounts of contaminants in a vacuum chamber, which simulates conditions in space such as extreme temperatures [3].…”
Section: Introductionmentioning
confidence: 99%
“…Extrapolating such 7-day isothermal ASTM-1559 data to a 15-year mission through an arbitrary power-law curve, or fitting 5-day temperature-step VBQC data through the sum of unjustified laws for 6 species is equally unsatisfactory. We have been convinced for many year now that the only way forward to really improve this state of the art is to perform a characterization at chemical species level, separating the contribution of each species to outgassing or deposit 1,2,3 . Whereas a total mass can easily be fitted by the sum of several laws regardless of their physical representativeness (exponentials for desorption or diffusion laws can usually equally do the job), a long-hoped-for independent measurement of each chemical species can probably only be discriminatorily fitted by the real physical law, the only one promising an accurate mission time extrapolation.…”
Section: Introductionmentioning
confidence: 99%